Answer:
B. 104 = x - [(-1182) + (-1144)]
Explanation:
The unknown entahlpy change for the given equation is determined by the Hess's Law.
3C + 3O2 → 3CO2 ΔH = -1182 kJ ....(a)
4H2 + 2O2 → 4H2O ΔH =-1144 kJ ....(b)
C3H8 → 3C + 4H2 ΔH = 104 kJ ....(c)
C3H8 + 5O2 → 3CO2 + 4H2O ΔH = x ....(d)
The unknown enthalpy change x is calculated as follows,
The equation (d) is obtained by the adding equation (a), equation (b ) and equation (c) .Therefore, the value of the unknown enthalpy change x will be equal to the sum of all enthalpy change value of the respective equation.
104 = x - [(-1182) + (-1144)]